Exploring the legend and the myth in ocean and maritime life: A systematic literature review - Olivia, Raisya Arzety; Ashari, Arif; Ervin, Muhamad; Hadi, Bambang Syaeful; Brotowiranti, Rayung Wulan; Reswari, Az-Zahra Ardhana; Yuangwidi, Kinanthi Purbaning; Salma, Greace Nanda Putri; Fitriana, Kamlia Nur; Abdullah, Nurul Hakimah Che; Zekeri, Fatihin Nabiha Mohd; Razali, Muhammad Syafiq (Universitas Negeri Yogyakarta, 2024)
Oceans cover about two-thirds of the Earth's surface and hold no less than 97% of the Earth's water. With this significant position, many mysteries still have yet to be revealed by various explorations and studies on the oceans. Here, we explore the oceans' and maritime world's legends and myths worldwide. This paper is a systematic literature review (SLR) organized using the PRISMA approach. Search keywords were determined using the PCC method. The documents reviewed were obtained from the Scopus database. A total of 436 documents were obtained, and 70 met the criteria based on selection in the extraction process and continued in the review stage. The findings of this study show that ocean and maritime myths are not always related to metaphysical myths. Some myths are philosophies of community life and semiotics. Myths related to metaphysics usually form local wisdom in the community. In summary, this study offers new insights into myths in the oceans, a topic that is still relatively rare in previous literature.